(untitled) (Journal of Informatics and Mathematical Sciences, 2025)
In the present note, we consider the value distribution of the product of a meromorphic function and its higher order derivatives and generalise a result of Lahiri and Dewan (Value distribution of the product of a meromorphic function and its derivative, Kodai Mathematical Journal 26 (2003), 95 – 100).